2017
DOI: 10.1093/jb/mvw092
|View full text |Cite
|
Sign up to set email alerts
|

The retinoic acid receptor-related orphan receptor α positively regulates tight junction protein claudin domain-containing 1 mRNA expression in human brain endothelial cells

Abstract: Members of the claudin family play important roles in the formation of tight junctions (TJs) in several tissues. Claudin domain containing 1 (CLDND1) is homologous to this family and localizes to TJs and the cytoplasm when exogenously expressed in cultured epithelial cell lines. Furthermore, serum antibody levels of CLDND1-derived peptides are elevated in patients with cerebral infection, cardiovascular disease or diabetes mellitus as compared to healthy controls. However, CLDND1 transcriptional regulation rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
1
17
1
Order By: Relevance
“…RORA shows a circadian expression and senses fatty acids, cholesterol, and oxysterols [95]. It is upregulated in the hippocampus of patients with Alzheimer’s disease [44] and also regulates the expression of the tight junction protein CLDND1 in human brain endothelial cells [96]. The cAMP responsive element binding protein 3-like 1 ( CREB3L1 ) gene codes for the membrane-bound ER stress transducer OASIS, which has an important role in osteoblast differentiation during bone development [97].…”
Section: Transcriptional Regulation Of Grinamentioning
confidence: 99%
See 1 more Smart Citation
“…RORA shows a circadian expression and senses fatty acids, cholesterol, and oxysterols [95]. It is upregulated in the hippocampus of patients with Alzheimer’s disease [44] and also regulates the expression of the tight junction protein CLDND1 in human brain endothelial cells [96]. The cAMP responsive element binding protein 3-like 1 ( CREB3L1 ) gene codes for the membrane-bound ER stress transducer OASIS, which has an important role in osteoblast differentiation during bone development [97].…”
Section: Transcriptional Regulation Of Grinamentioning
confidence: 99%
“…RORA shows a circadian expression and senses fatty acids, cholesterol, and oxysterols [95]. It is upregulated in the hippocampus of patients with Alzheimer’s disease [44] and also regulates the expression of the tight junction protein CLDND1 in human brain endothelial cells [96].…”
Section: Transcriptional Regulation Of Grinamentioning
confidence: 99%
“…In brain endothelial cells, claudin domain containing 1 (CLDND1), which is involved in tight junction formation, is regulated at the transcriptional level by RORα and at the post-transcriptional level by miR-124 [29,30]. Moreover, decreased CLDND1 expression in the adult murine cerebellum results in cerebellar hemorrhage [31].…”
Section: Introductionmentioning
confidence: 99%
“…Tight junctions are a type of cell-to-cell adhesion in epithelial or endothelial cell sheets, forming continuous seals around cells and functioning as a physical barrier to prevent solutes and water from passing freely through the paracellular space (7). Tight junctions maintain cell polarity by preventing the lateral diffusion of integral membrane proteins between the lateral/basal and apical surfaces, allowing the specialized functions of each surface to be preserved (8). It has also been reported that tight junctions are associated with cellular survival, proliferation, migration and differentiation (9).…”
Section: Introductionmentioning
confidence: 99%